DESIGN AS GENERATOR (DAG): AN ARCHITECTURAL APPROACH FOR EMPOWERING COMMUNITY - Martin, KATOPPO; Ruth, OPPUSUNGGU; Phebe, VALENCIA; Sugeng, TRIYADI (DIMENSI (Journal of Architecture and Built Environment), 2014)
Design as we imagine should act like a generator, to become light for others. This is the concept of Design as Generator (DAG). It main goal is for bring the essence of Architecture in which to enhance the quality of life not just for self but for others. For this purpose we create D-Apps (Dwelling Applications), D-PaD and A-PaD (Dwelling and Area Prototype Applicative Design) that will explained by our experimental dwelling project 200 Rumah Besi and our future project taki (taman kita) Community Sustainable Park. We also developed DAG particular empowering and participatory design methodology – inspired by PAR (Participatory Action Research) and DT (Design Thinking) through mixed methods research, the Sequential Embedded Experimental Model.